PH‐Dependent Cancer‐Directed Photodynamic Therapy by a Water‐Soluble Graphitic‐Phase Carbon Nitride–Porphyrin Nanoprobe. Issue 6 (9th May 2016) - Chan, Chi‐Fai; Zhou, Yan; Guo, Hongyu; Zhang, Junying; Jiang, Lijun; Chen, Wei; Shiu, Kwok‐Keung; Wong, Wai‐Kwok; Wong, Ka‐Leung
Abstract: Theranostic photodynamic nanomaterials suffer from poor water solubility and nontargeted toxicity. A water‐soluble graphitic‐phase carbon nitride‐based material (g‐C3 N4 ) conjugated to a positively charged porphyrin P2 (conjugating concentration: 60 μm mg −1 mL −1 ) is shown to be a new concept of photodynamic therapeutic agent (g‐C3 N4 –P2). The pH‐sensitive emission of g‐C3 N4 is the driving force for the generation of 1 O2 from g‐C3 N4 –P2. The amount of 1 O2 /light generated from a photosensitizer porphyrin can be controlled by the pH‐sensitive emission of g‐C3 N4 at acidic pH (pH 4–6), especially under acidic conditions mimicking those of tumor tissue, and thus has the potential to be utilized as a cancer‐selective PDT agent. Abstract : To be taken lightly : A porphyrin‐conjugated graphitic‐phase carbon nitride (g‐C3 N4 ) nanoprobe was synthesized and it was found to generate singlet oxygen upon irradiation in a pH‐dependent fashion in cancer cells. The synthesis, photophysical characterization and evaluation of the light‐induced toxicity of this g‐C3 N4 –porphyrin conjugate in a range of cell types is reported.